“Thomas Hardy’s Dialect in Spanish Translation: The Reception of ‘Tess of the D’Urbervilles’” - Braga Riera, Jorge (Status Quaestionis, 2017)
Thomas Hardy’s use of the Wessex county dialect plays a key role in much of his narrative fictional dialogue, as shown in Tess of the D’Urbervilles (1891). By analysing the two existing Spanish translations of this novel (one by M. Ortega y Gasset, first published in 1924 and recently reedited and revised by Carmen Criado; the other by Javier Franco Aixelá in 1994), this paper is intended to illustrate how the grammatical structures, vocabulary, and phonological characteristics of such dialect are rendered into Spanish. Attempts will be made to show the mechanisms that the translators resort to in order to convey those dialectal features and the extent to which they have managed to portray both Tess’s rural quality and social evolution as reflected in her idiom.